Behaviour of Rista (meatballs cooked in spiced curry) under aerobic refrigerated storage conditions: Behaviour of Rista (meatballs cooked in spiced curry) - Irshad, S; Ahmad, Sheikh Rafeh; Sofi, AH; Wani, SA; Maqbool, S; Beigh, YA; Andrabi, M; Wani, IA; Sajad, S; Nazir, T (Journal of Meat Science, 2023)
The present study was conducted to study the effect of aerobic packaging system on the storage stability of Rista (meatballs cooked in spiced curry) under refrigeration temperature. A total of three types of Rista developed including: T0 as control Rista (lean meat: animal fat = 90:10 in the formulation), T1 as fiber rich Rista (lean meat: animal fat: Hydrated Wheat Bran=82:10:8 in the formulation) T2 as antioxidant rich Rista (lean meat: animal fat=90:10 in the formulation and fortified with 0.1% Grape Seed Extract) were packaged aerobically in LDPE pouches and stored at refrigeration temperature (4±1oC). The samples were analysed during storage (on days 0, 7, 10, 13, 16, 19). The results revealed that the emulsion stability (%), cooking yield (%), pH and water activity presenting the mean of 93.67, 95.61, 94.47; 91.59, 95.49, 93.38; 6.29, 6.65, 6.54 and 0.98, 0.99, 0.99 in T0, T1 and T2, respectively. The sensory values for various sensory parameters viz appearance, flavour, texture, saltiness and overall acceptability followed a decreasing trend with the storage. The microbial parameters like Standard Plate Count (SPC) increased significantly throughout the storage period; Total Psychrotrophic Count (TPSC) was detected from 13th day of storage and Coliform Count was not detected throughout the storage period. The observations concluded that the product can be stored in aerobically packaged LDPE pouches for 16 days without much change in physicochemical, microbiological and sensory properties at refrigerated storage.
Keywords: Antioxidant Fiber; Meatballs; Refrigeration; Rista